Objective methods of diagnosing myofascial pain syndrome - Tomasz Piętka; Grzegorz Onik; Katarzyna Knapik; Karolina Sieroń (Medycyna Ogólna i Nauki o Zdrowiu, 2021)
Introduction and objective The myofascial pain syndrome (MPS) is an important clinical problem which, despite numerous scientific reports, remains not fully understood. This refers in particular to unclearly stated pathomechanism and undefined diagnostic and therapeutic standards. In daily clinical practice, palpation is the most commonly applied method of myofascial pain syndrome diagnostics. However, this may be associated with inaccurate diagnosis. Therefore, the diagnosis of myofascial pain syndrome requires reliable, repeatable measurements which should be characterized by high sensitivity in order to detect clinically important changes. The aim of this study is to review the objective diagnostic methods essential for the correct diagnosis of myofascial pain syndrome.